2001
DOI: 10.1111/j.1469-7793.2001.0521k.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in contractile properties of human skeletal muscle induced by joint immobilization

Abstract: The effects of joint immobilization on the contractile properties of human skeletal muscle were examined using the first dorsal interosseous (FDI) muscle. The middle finger, index finger and thumb were immobilized for a period of 6 weeks, and the contractile properties of FDI were tested before immobilization, after 3 and 6 weeks of immobilization, and after a 6 week recovery period. Twitch and tetanic contractions of FDI were evoked by per‐cutaneous electrical stimulation. The peak twitch tension (Pt), contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 44 publications
7
46
1
1
Order By: Relevance
“…This finding, which is likely to be related to disuse atrophy, is in accordance with previous experimental reports of skeletal muscle changes after upper-limb immobilization (Desaphy et al, 2001;Seki et al 2001a;2001b).…”
Section: Motor Maps and Mep Recruitment Curvessupporting
confidence: 93%
See 1 more Smart Citation
“…This finding, which is likely to be related to disuse atrophy, is in accordance with previous experimental reports of skeletal muscle changes after upper-limb immobilization (Desaphy et al, 2001;Seki et al 2001a;2001b).…”
Section: Motor Maps and Mep Recruitment Curvessupporting
confidence: 93%
“…Animal studies suggest that sensory impoverishment may determine changes in the organization and size of cortical receptive fields in the somatosensory cortex (Coq and Xerri, 1999;Langlet et al, 1999). The vast majority of studies on the effects of long term immobilization in humans have examined changes in the contractile properties of skeletal muscle (Desaphy et al, 2001;Seki et al, 2001b) or motor units (Seki et al, 2001a). Only two reports to date have documented central motor changes in neurologically normal subjects who wore splints for more than four weeks because of fractures of the wrist (Zanette et al, 1997) or the leg (Liepert et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The MMG signals originated in the skeletal muscle come from the mechanical vibrations generated by the muscular shocks of the APs (Yoshitake et al, 2002), which combined with MUs lead to MVC (tetany) (Neering et al, 1991;Seki et al, 2001). In this study, the thicker layers of body fat increased the distance between sensor and muscle, and the physical aspects of the fat acted as a low-pass filter, attenuating the MMG signal, as demonstrated by the analyzed parameters.…”
Section: Discussionmentioning
confidence: 86%
“…The first studies were conducted on participants who wore splints either at the upper limb or the lower limb for 4−6 weeks because of fractures (Kaneko, Murakami, Onari, Kurumadani, & Kawaguchi, 2003;Liepert, Tegenthoff, & Malin, 1995;Seki, Taniguchi, & Narusawa, 2001a, 2001b. Long-term joint immobilization is known to modify the proportion of fast and slow muscle fibers and thus the contractility of skeletal muscle (Bey et al, 2003;Seki et al, 2001a) and perhaps to change the intrinsic properties of motor neurons and the input to motor neurons from peripheral afferents (Seki et al, 2001b). Although the results of some electrophysiological studies have suggested that changes of neural excitability at both central and peripheral levels may occur only after weeks or even months of immobilization, immobilization indeed induces modification of the sensorimotor input and motor behavior as soon as the cast is applied.…”
mentioning
confidence: 99%